Influence of brassinosteroids on the formation of phosphatidic acid in vivo in wheat - Derevyanchuk, M.V.; Litvinovskaуа, R.P.; Chornomorchenko, S. S.; Khripach, V.A.; Kravets, V. S.; Kukhar, V.P. (Reports of the National Academy of Sciences of Ukraine, 2015)
The effect of brassinosteroids (BRs) on the formation of a lipid messenger, phosphatidic acid (PA), is investigated in vivo. It is observed that BRs significantly increase the PA level in 20 min after the treatment of plant tissues with 24-epibrassinolide. Inhibition of 1,2-diacylglycerol kinases decreases the PA accumulation and increases the diacylglycerol pool in response to BRs. BRs induce not only the processes of PA formation, but also its further dephosphorylation into DAG by lipid phosphatases. Our results indicate the BRs involvement in the regulation of a phospholipid signaling and the levels of lipid signaling mediators in plant cells, particularly PA.